2008
DOI: 10.1136/jech.2008.077115
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a social support intervention on infant feeding practices: randomised controlled trial

Abstract: Background: To assess whether monthly home visits from trained volunteers could improve infant feeding practices at age 12 months, a randomised controlled trial was carried out in two disadvantaged inner city London boroughs. Methods: Women attending baby clinics with their infants (312) were randomised to receive monthly home visits from trained volunteers over a 9-month period (intervention group) or standard professional care only (control group). The primary outcome was vitamin C intakes from fruit. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(130 citation statements)
references
References 23 publications
2
128
0
Order By: Relevance
“…5 However, none of the four UK based randomised controlled trials and the one quasi-randomised trial were able to show significant improvements in any or exclusive breastfeeding rates. [6][7][8][9][10] We hypothesised that differences in effects between studies may result from different levels of routine support for breast feeding in different settings or the intensity or timing of the delivery of the peer support intervention. It is probable that in settings where the routine level of support for breastfeeding mothers is high, more intensive interventions would be required to achieve an effect.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, none of the four UK based randomised controlled trials and the one quasi-randomised trial were able to show significant improvements in any or exclusive breastfeeding rates. [6][7][8][9][10] We hypothesised that differences in effects between studies may result from different levels of routine support for breast feeding in different settings or the intensity or timing of the delivery of the peer support intervention. It is probable that in settings where the routine level of support for breastfeeding mothers is high, more intensive interventions would be required to achieve an effect.…”
Section: Introductionmentioning
confidence: 99%
“…33 This review found these interventions to be effective in increasing breastfeeding maintenance in low-or middle-income countries, reducing the risk of not exclusively breastfeeding by up to 28%. However, the UK-based RCTs of BFPS interventions included in this review did not find increases in breastfeeding continuation rates, [34][35][36][37] with no increase in breastfeeding maintenance at 8-10 weeks 35,37 and 4 months.…”
Section: Breastfeeding Peer-support Interventionsmentioning
confidence: 93%
“…Four UK RCTs, [34][35][36][37] both individual and cluster randomised trials, had already demonstrated that it was feasible and acceptable to randomise pregnant women in the antenatal period to receive either BFPS or usual care. Two RCTs that randomised individuals recruited 70% 35 and 82% 34 of their intended sample size and cited difficulties in recruitment resulting from resource constraints.…”
Section: Mam-kind: a Uk Feasibility Studymentioning
confidence: 99%
See 2 more Smart Citations